Introduction of Posterior Axilla Sling Traction in Simulated Shoulder Dystocia - Julie R. Whittington; Aaron T. Poole (Thieme Medical Publishers, Inc., 2018)
Abstract Objective Aim of this study was to introduce posterior axilla sling traction (PAST) in delivering providers and nursing staff as an adjunct to the management of shoulder dystocia and evaluate comfort in performing the maneuver. Methods A presimulation questionnaire had given to all participants. A brief training on how to perform PAST was also given. A simulated shoulder dystocia was run where usual maneuvers failed. Participants used PAST for delivery of posterior shoulder, delivery of posterior arm, and to assist with rotation. Participants were then given a post-simulation questionnaire. A Chi-squared test was used to evaluate comfort with performing the procedure pre and post-simulation. Results Data were collected from 43 participants at pre and post-simulation. Designations (attending, resident, midwife, registered nurse) and responses were recorded to the questionnaires. There was a statistically significant increase in the number of providers and nurses who would feel comfortable using PAST for shoulder dystocia management and for rotational maneuvers. Ninety-three percent of participants would consider using PAST in future shoulder dystocia when usual maneuvers failed. Conclusion PAST is an adjunct to management of shoulder dystocia that has not previously been taught in our facility. The majority of participants in our simulation felt comfortable with using PAST.